PENGARUH OPINI AUDIT DAN TEMUAN AUDIT TERHADAP TINGKAT KORUPSI DI PEMERINTAH PROVINSI PAPUA - Vinsensius Jehandu; Agustinus Salle; Paulus K Allo Layuk (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2019)
The purpose of the study is to identify the relationship between public perceptions about audit opinion, audit findings and the level of corruption in Papua Province (Case Study of the Government of Keerom Regency, Jayapura Regency and Sarmi Regency). A sample of 120 respondents consisted of 40 respondents from each district. Data collection techniques through questionnaires and data analysis using the Partial Least Square (PLS) approach. The results showed the greater the perception of audit opinions the greater the trust in corruption handled by the auditor. Meanwhile, the results of the study showed that the magnitude of audit findings carried out by BPK influenced the level of corruption that occurred. Audit findings can detect corruption in the government and local government efforts to make improvements according to the auditor's recommendations can significantly reduce the level of corruption.